Design of floatable monolithic breakwater structure to ensure tranquility in port and harbor basins - Sebastian, Anjali; S, Sruthy; Thuvassery, Jayadeep (International Journal of Engineering and Technology, 2018)
The objective of this paper is to present the selection, the detailing and optimal design of a floatable monolithic breakwater structure at Ponnani harbour in Kerala, India. Ponnani fishery harbour is an estuarine harbour and the breakwaters here serve the main purpose of river training bunds. Studies on preliminary analysis of tranquility condition in front of the wharf structure at Ponnani fishery harbour was conducted jointly by the Investigation subdivision, Beypore and Centre for Water Resources Development and Management (CWRDM), Pune. It has been noticed that due to seasonal variation in the wave directions, wave heights inside the basin areas and near the water front structures of the harbour are not within the permissible limits. A floating breakwater structure (FBS) is suggested to change the direction of waves and surges with seasons.The present proposal consists of construction of a floatable monolithic breakwater structure of length 70m. A pile restrained pontoon floating breakwater structure is adopted for Ponnani harbour. The ability of FBS to attenuate the incident wave is determined by calculat-ing the transmission coefficient. Theoretical formulas are used to check the effectiveness of the suggested FBS. The FBS has been mod-elled, analysed and arrived at an optimal design using the ANSYS software.Â Â